Retinal microangiopathy in arterial hypertension as an early marker of a cerebral macroangiopathy - Michelson, Georg; Engelhorn, Tobias; Dörfler, Arnd (Deutsche Medizinische Wochenschrift, 2011)
A 54-year-old man reported having had nonspecific attacks of dizziness. His BMI was 27.7. Since 11 years he had been treated for arterial hypertension and had received oral medication for type 2 diabetes for one year. The latest blood pressure value was 134/109 mm Hg during treatment with a combination of atenolol, chlortalidone und hydralazine-HCl; furthermore hr received simvastatin, metformin, glimepirid und ramipril. A standardized telemedical imaging of the retina ("talkingeyes (®) ") was undertaken, revealing focal and generalized arteriolar narrowing of the retinal vessels and a retinal microinfarction (cotton wool spot) in the right eye. The arterial/venous ratio was decreased to 0.74 in the right and 0.77 in the left eye.Optical coherence tomographie (OCT) revealed an ischemic microinfarction of the retina with marked axonal swelling. The digital subtraction angiography of the cerebral vessels revealed a 40 % stenosis of the right internal carotid artery and a proximal, highgrade stenosis of the basilary artery.Angioplasty with stent insertion of the basilary artery was performed. Long-term observation showed no restenosis and a reduction in the size of the the retinal microinfarct.Retinal microinfarctions denote localized retinal areas of hypoxia and underperfusion. They may act as markers of a generalized micro- and macroangiopathy. Patients with severe retinal microangiopathic changes should be examined thoroughly to detect early macroangiopathic changes. These can be treated by interventional procedures thus avoiding irreversible end-organ damages.
EVALuna2:21059